Spurious Galois fields - Kościelny, Czesław (Zielona Góra: Uniwersytet Zielonogórski)
An algebraic system consisting of a finite set of "q" elements with two internal binary operations of addition and multiplication is studied. For the described system, which satisfies all the axioms of the fields except for the axiom of associativity of addition, which may, but need not, be assured, the name spurious Galois field and the symbol "SGF(q)" are proposed.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka